2011
DOI: 10.1007/s10886-011-9910-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex Pheromone and Trail Pheromone of the Sand Termite Psammotermes hybostoma

Abstract: Within the complex network of chemical signals used by termites, trail pheromones and sex pheromones are among the best known. Numerous recent papers map the chemical identity and glandular origin of these pheromones in nearly all major isopteran taxa. In this study, we aimed to describe the sex pheromone and the trail pheromone of a poorly known sand termite, Psammotermes hybostoma. We identified (3Z,6Z,8E)-dodeca-3,6,8-trien-1-ol (dodecatrienol) as the sex pheromone released by tergal and sternal glands of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…Some studies also showed that both (Z,Z)-dodeca-3,6-dien-1-ol and (Z)-dodec-3-en-1-ol are the components of the trail-following pheromone used by workers in O. formosanus (data not shown). These results underline the evolutionary parsimony between the trail-following pheromones of workers and the sex-pairing pheromones of imagoes (Bordereau et al, 1991(Bordereau et al, , 2010Robert et al, 2004;Sillam-Dussès et al, 2011).…”
Section: Discussionsupporting
confidence: 56%
“…Some studies also showed that both (Z,Z)-dodeca-3,6-dien-1-ol and (Z)-dodec-3-en-1-ol are the components of the trail-following pheromone used by workers in O. formosanus (data not shown). These results underline the evolutionary parsimony between the trail-following pheromones of workers and the sex-pairing pheromones of imagoes (Bordereau et al, 1991(Bordereau et al, , 2010Robert et al, 2004;Sillam-Dussès et al, 2011).…”
Section: Discussionsupporting
confidence: 56%
“…The chemical structure of the trail pheromone is the same than the one of the sex-pairing pheromone secreted by females of O. formosanus [29]. The identical chemical nature of the trail pheromone and the sex pheromone within a species has been reported in other species, such as (3 Z ,6 Z ,8 E )-dodeca-3,6,8-trien-1-ol in Psammotermes hybostoma [38], and syn -4,6-dimethyldodecanal in Zootermopsis nevadensis and Z. angusticollis [39]. This parsimonious use of the pheromone compounds within termite species is reinforced by the use of the same compounds among different species.…”
Section: Discussionmentioning
confidence: 63%
“…Open-field Y-shaped trail-following bioassays were performed on damp filter paper discs with a 120° angle between each branch, as described by Sillam-Dussès et al [38], Hall et al [45], and Traniello et al [8] (Figure S5). On the stem (3 cm) and/or on one of the Y branches (5 cm), a trail was drawn with a microliter syringe containing extract, standards or hexane control.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its phylogenetic position, its peculiar biology, and pest status [30], very few studies have attempted to improve the basic knowledge of Psammotermes. Here, in the continuity of the recent characterization of Psammotermes hybostoma trail-following pheromone, sex-pairing pheromone, and soldier defensive secretion [3], [31], we investigate its caste developmental system. Two previous studies emphasized the enormous polymorphism of Psammotermes soldiers and apterous immatures [32], [33], but provided only superficial insights into the developmental scheme.…”
Section: Introductionmentioning
confidence: 99%